Corpus-Based Contrastive Studies of English and Chinese. - McEnery, Tony (Routledge Advances in Corpus Linguistics, 2010)
This book is concerned with cross-linguistic contrast of major grammatical categories in English and Chinese, two most important yet genetically different world languages. This genetic difference has resulted in many subsidiary differences that are, among other things, related to grammar. Compared with typologically related languages, cross-linguistic contrast of English and Chinese is more challenging yet promising. The main theme of this book lies in its focus on cross-linguistic contrast of aspect-related grammatical categories, or, grammatical categories that contribute to aspectual meanin.